Effect of Graded Levels of Dried Pawpaw (Carica papaya) Seed on the Performance, Haematology, Serum Biochemistry and Carcass Evaluation of Chicken Broilers - Bolu, S.A.O.; Sola-Ojo, F.E.; Olorunsanya, O.A.; Idris, K. (International Journal of Poultry Science, 2009)
A feeding trial was conducted to investigate the effect of graded levels of Dried Pawpaw Seed (DPS) on growth performance, haematological parameters and carcass evaluation of chicken broilers. One hundred day-old broilers were randomly divided into four treatments groups of diets containing 0, 5, 10 and 15% DPS in a Completely Randomized Designed (CRD) for a period of six weeks. The results of this experiments showed that there were significant differences (p>0.05) in feed intake and weight gain across the dietary treatment with diet containing 5% DPS having the highest weight gain of 17.58g/bird/day, while birds fed diets with 15% DPS had the lowest weight gain (11.18 g/bird/day), nutrient utilization was higher in birds fed 5% DPS. There were significant differences (p